2012
DOI: 10.1111/j.1365-2613.2012.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Ruminant organotypic brain‐slice cultures as a model for the investigation of CNS listeriosis

Abstract: Summary Central nervous system (CNS) infections in ruminant livestock, such as listeriosis, are of major concern for veterinary and public health. To date, no host‐specific in vitro models for ruminant CNS infections are available. Here, we established and evaluated the suitability of organotypic brain‐slices of ruminant origin as in vitro model to study mechanisms of Listeria monocytogenes CNS infection. Ruminants are frequently affected by fatal listeric rhombencephalitis that closely resembles the same cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…We hypothesized that this may in part be related to the ability of the agent to spread intracere- brally inside axons, allowing the agent to escape the immune response at least temporarily. As our previously reported neuropathological observations and infection assays of hippocampal brain slices suggested that intra-axonal spread of L. monocytogenes may also occur in the CNS (17,30), the present study was designed to explore this hypothesis by neuroanatomical mapping of the lesions, precise localization of L. monocytogenes bacteria, and in vitro infections of brain cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that this may in part be related to the ability of the agent to spread intracere- brally inside axons, allowing the agent to escape the immune response at least temporarily. As our previously reported neuropathological observations and infection assays of hippocampal brain slices suggested that intra-axonal spread of L. monocytogenes may also occur in the CNS (17,30), the present study was designed to explore this hypothesis by neuroanatomical mapping of the lesions, precise localization of L. monocytogenes bacteria, and in vitro infections of brain cells.…”
Section: Discussionmentioning
confidence: 99%
“…The efficient spread of L. monocytogenes could be explained by its ability to move from cell to cell, which permits the agent to multiply and diffuse within tissues protected from the host defenses by avoiding contact with the extracellular compartment (19). In view of the observed ability of L. monocytogenes to spread within cranial nerves (25,26), our previous studies showing progression of the lesions within the brain (17) and the sporadic association of L. monocytogenes with axons in the hippocampal slice model (30), we hypothesized that intercellular spread of the agent in the CNS could also be intra-axonal. Moving within axons, a highly interconnected network with little or no major histocompatibility complex (MHC) expression (29,31), would, at least temporarily, allow L. monocytogenes to escape immune detection while efficiently spreading to distant CNS regions.…”
mentioning
confidence: 99%
“…In fact, in one study, peripheral neurons were able to be effectively infected, contrary to hippocampal neurons, which were resistant, suggesting that different types of neurons might have different susceptibilities to bacterial tropism. 13,17 A recent animal study, however, suggests that once the bacteria have gained access to the CNS via the peripheral nervous system, the infection can spread along the axons, producing additional lesions. 17,32 This hypothesis has not previously been evaluated in humans.…”
Section: Fig 3 Fused Images Generated From Swi and Combined Fractiomentioning
confidence: 99%
“…13,17 A recent animal study, however, suggests that once the bacteria have gained access to the CNS via the peripheral nervous system, the infection can spread along the axons, producing additional lesions. 17,32 This hypothesis has not previously been evaluated in humans. Our results based on MRI in cases of multiple brain abscesses strongly suggest that this intraneural mechanism of spreading in the CNS also applies to humans.…”
Section: Fig 3 Fused Images Generated From Swi and Combined Fractiomentioning
confidence: 99%
See 1 more Smart Citation